NILAI KETAKTERATURAN TOTAL SISI DARI GRAF SEGITIGA BERMUDA - Anjelia, Novalita; Slamin, S; Dafik, D (KadikmA, 2014)
Abstract.For a simple graph G, a labelling Î»â¶V(G)âªE(G)â {1,2,â¦,k} is called an edge irregular total k-labelling of G if for any two different edges e and f of G there is, wt(e)â wt(f). The total edge irregularity strength denoted by tes G is the smallest positive integer k for which G has an edge irregular total k-labelling. In this paper, we consider the total edge irregularity strength of Bermuda Triangle graph and the union isomorphic and non isomorphic Bermuda Triangle graph. We show that tes(ãBtrã_(n,4) )= â(30n+17)/3â, for nâ¥1, tes(ãsBtrã_(n,4) )=â(s(30n+15)+ 2)/3â, for nâ¥1 and sâ¥2, and tes(ãBtrã_(n,4)âªãBtrã_(m,4) )=â((30n+15)+ (30m+15)+ 2)/3â, for 1â¤nâ¤m. Keywords:Edge irregular total labelling, Irregularity strength, Total edge irregularity strength, Bermuda Triangle graph.